Does User Preference Matter? A Comparative Study on Influencing Factors of User Activity Between Government-Provided and Business-Provided Apps - Guo, Yuanyuan (Frontiers in Psychology, 2022)
The competition between government-provided apps and business-provided apps for active users in China is becoming increasingly fierce. Apps with higher user activity will win this competition. To maintain active users, finding the user activity influencing factors is crucial. In this study, we selected a government-provided app—"Beijing One Card" and a business-provided app—"Bus Code" (Beijing area) in the field of public transportation as the comparative research objects. Based on multiple regression analysis, we explored the factors influencing user activity. We found user preference plays a critical role in distinguishing the influencing factors of user activity between two kinds of apps. Distinct from the existing research, the service quality does not affect the user activity of public transportation apps. This paper argues that whether it is a government-provided app or a business-provided app, to enhance the user activity of the app, in the short term, it is necessary to improve the app function according to the user's needs, try to provide services which users like, cater to user's preference, strengthen their use experience; In the long run, it is essential to pay attention to mining the user's data that accumulated during operating the app to understand citizens behavior. So as to affect the user's preference, enhance citizen trust and improve citizen participation through public policy.